1977
DOI: 10.1128/aac.11.4.609
|View full text |Cite
|
Sign up to set email alerts
|

Netilmicin and Gentamicin: Comparative Pharmacology in Humans

Abstract: Thirteen male subjects received 1 mg of either gentamicin or netilmicin per kg, first intramuscularly and then intravenously. After the intramuscular dose, concentrations of gentamicin in the serum were more variable than those of netilmicin. After the intravenous dose, the distribution phase of netilmicin was twice as rapid as gentamicin. The average half-times of the elimination phase were similar, but there was marked variability among the subjects receiving gentamicin. Serum clearance of netilmicin was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0
1

Year Published

1978
1978
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
(20 reference statements)
2
17
0
1
Order By: Relevance
“…Total body clearance calculated from our data was comparable to that reported in two studies (3,5). Although our rate was slower than that reported in three other studies (6,7,10), this is presumed to be due to the method of calculation and route of administration as noted for volume of distribution. Renal clearance in our study is somewhat lower than that previously reported (6, 10), but we observed a large intersubject variation, as did another investigator (5).…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…Total body clearance calculated from our data was comparable to that reported in two studies (3,5). Although our rate was slower than that reported in three other studies (6,7,10), this is presumed to be due to the method of calculation and route of administration as noted for volume of distribution. Renal clearance in our study is somewhat lower than that previously reported (6, 10), but we observed a large intersubject variation, as did another investigator (5).…”
Section: Resultssupporting
confidence: 47%
“…2) constant for netilnicin, calculated by a two-compartment model (5), have been reported. After intravenous administration of the drugs, the pharmacokinetics of gentamicin (1, 7) and netilmicin (3,5,7,11) have been described by a twocompartment model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical advantages of netilmicin are threefold: (i) an increased in vitro bactericidal activity over gentamicin against many strains of Enterobacteriaceae (1-3, 5, 6, 10, 11, 13, 15-17, 20, 22, 23); (ii) the inhibition of gentamicin-resistant strains when the resistance is associated with one of the gentamicininactivating acetylases (aminoglycoside acetylase-3i, -ii, or -iii) or an adenylase (aminoglycoside nucleotidylase-2"), which have been common modes of resistance among Enterobacter species, Escherichia coli, and Pseudomonas aeruginosa (4,16,18); (iii) relative freedom from ototoxicity and reduced nephrotoxicity in experimental animals (12,20). Also, there is a suggestion that the serum levels may be more predictable than those of gentamicin (19). These favorable features of netilmicin suggest the possibility of more effective therapy of serious gram-negative bacterial infections with diminished drug toxicity and formed the basis for the investigations reported here.…”
mentioning
confidence: 85%
“…The pharmacology of netilmicin is similar to that of gentamicin (9,14,25), but the alpha phase of netilmicin is more rapid than that of gentamicin (27), and higher doses (2 mg/kg per 8 h) have been recommended to achieve equivalent serum levels (9). Initial serum levels were predictable in only a small majority of our patients, although levels were less variable than gentamicin in another study (26).…”
Section: Resultsmentioning
confidence: 86%